Murder, anyone? [videorecording (DVD)] - Bressack, Gordon; Andrews, Kristos; Stineman, Galadriel; Lamarche, Maurice (Uncork'd Entertainment, 2025)
Two Playwrights are tasked with creating the next avant-garde thriller; but as they write, the story comes to life and their own emotions and arguments begin to manifest on film.